The conjuring 3. [videorecording (DVD)] The devil made me do it - Farmiga, Vera; Wilson, Patrick, 1973-; O'Connor, Ruairi (Warner Bros. Home Entertainment, 2021)
A chilling story of terror, murder, and unknown evil that shocked even experienced, real-life paranormal investigators. One of the most sensational cases from their files, it starts with a fight for the soul of a young boy, then takes them beyond anything they'd ever seen before, to mark the first time in U.S. history that a murder suspect would claim demonic possession as a defense.